FEATURES OF TREATMENT OF PURULENT-NECROTIC COMPLICATIONS OF ACUTE PANCREATITIS - Ursol , Grigoriy; Shulyk , Mykola; Sobchenko , Dmytro; Ursol , Luka (Collection of scientific papers «ΛΌГOΣ», 2025)
Introduction. A literature review indicates that acute pancreatitis is one of the most pressing surgical diseases due to its increasing incidence and widespread prevalence. The issue becomes even more critical due to the significant number of destructive forms of acute pancreatitis. The primary causes of mortality and complications in destructive forms are diagnostic errors, untimely surgical intervention, or inadequate surgical volume. These challenges stem from difficulties in determining the form of acute pancreatitis and the presence and nature of complications [1]. The development of purulent-septic complications significantly worsens the prognosis of the disease and, in some cases, poses a direct threat to the patient’s life due to toxic aggression and pronounced endogenous intoxication. Endogenous contamination predominates due to abscess formation and necrosis, highlighting the necessity of intensive therapy and minimally invasive treatment methods.